2023
DOI: 10.3389/fepid.2023.1109853
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of care and survival for lung cancer: Results of the European population-based high-resolution study

Abstract: ObjectivesTo investigate differences in lung cancer (LC) management and survival using data from European population cancer registries.MethodsWe analysed 4,602 lung cancer cases diagnosed in 2010–2013, followed-up to 2019 in five countries. Multivariable logistic regression was used to calculate the Odds Ratio (OR) of surgery for stages I–II LC or chemo- or radiotherapy for stages III–IV LC. Relative survival (RS) was estimated by the actuarial method; Relative Excess Risk of death (RER), with 95% CI, was calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Elderly (here defined as ≥70 years) represent a high proportion of lung cancer patients in Europe. In a large patterns of care analysis with >4500 patients, Sant et al reported that 46.9% were elderly [4]. At the same time, higher age is associated with relevant physiologic changes in the thoracic organs (e.g., reduced chest wall compliance) and further organ systems (e.g., kidney function) [3,[5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elderly (here defined as ≥70 years) represent a high proportion of lung cancer patients in Europe. In a large patterns of care analysis with >4500 patients, Sant et al reported that 46.9% were elderly [4]. At the same time, higher age is associated with relevant physiologic changes in the thoracic organs (e.g., reduced chest wall compliance) and further organ systems (e.g., kidney function) [3,[5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…Higher age is associated with an increased risk of lung cancer [3]. In a patterns of care study on lung cancer across Europe by Sant et al,46.9% of the patients were ≥70 years old [4].…”
Section: Introductionmentioning
confidence: 99%